Protocol for a multicentre, dual prospective and retrospective cohort study investigating timing of ileostomy closure after anterior resection for rectal cancer: The CLOSurE of Ileostomy Timing (CLOSE-IT) study. Issue 10 (15th October 2018) - Vaughan-Shaw, Peter G; Gash, Katherine; Adams, Katie; Vallance, Abigail E; Pilkington, Sophie A; Torkington, Jared; Cornish, Julie A
Abstract : Introduction: A defunctioning ileostomy is often formed during rectal cancer surgery to reduce the potentially fatal sequelae of anastomotic leak. Once the ileostomy is closed and bowel continuity restored, many patients can suffer poor bowel function, that is, low anterior resection syndrome (LARS). It has been suggested that delay to closure can increase incidence of LARS which is known to significantly reduce quality of life. Despite this, within the UK, time to closure of ileostomy is not subject to national targets within the National Health Service and delay to closure exceeds 18 months in one-third of patients. Clinical factors, surgeon and patient preference or service pressures may all impact time to closure, yet to date no study has investigated this. The aim of this UK-wide study is to assess time to ileostomy closure and identify reasons for delays. Methods and analysis: A UK-wide multicentre prospective snapshot study, together with retrospective analysis of ileostomy closure through The Dukes' Club Research Collaborative including patients undergoing ileostomy closure in a 3-month period (April to June 2018) and all patients who underwent anterior resection and ileostomy formation over a historical 12-month period (2015). Time to closure and incidence of 'non-closure' will be calculated. Units will be surveyed to determine local clinical and management protocols and barriers to timely closure. Multivariate linear regression analysis will be used to determine factors significantly associated with delay to ileostomy closure. Ethics and dissemination: Study approved by the South West-Exeter Research Ethics Committee and the Health Research Authority. Study results will be submitted for presentation at international conferences and for publication in peer-reviewed journals. Results will be presented to and discussed with the patient and public representatives and relevant national bodies to facilitate the development of consensus guidelines on optimum treatment pathways.